SELECTING MATERIALS AND DEVELOPING EXERCISES FOR TEACHING READING AT JUNIOR HIGH SCHOOL - RISMA KARTIKA DEWI; MOHAMMAD ABDUL RASYID (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2016)
This paper is aimed to discuss how to select appropriate texts which fulfill the aspects to represent students’ competence. To help the students comprehend the texts, the following texts and exercises are expected to be applicable for teaching reading at Junior High School. Building Knowledge of Field (BKOF), Modeling of Text (MOT), Joint Construction of Text (JCOT), and Independent Construction of Text (ICOT) are four stages suggested in teaching English.